2008
DOI: 10.1007/s00701-008-1561-6
|View full text |Cite
|
Sign up to set email alerts
|

Inflation-deflation method for endoscopic evacuation of intracerebral haematoma

Abstract: The inflation-deflation method using a combined irrigation-coagulation suction tube can facilitate optimal evacuation of ICH with secure haemostasis. Although further accumulation of patients and careful analyses are needed to be known whether this procedure improves the clinical outcomes in the patients, the preliminary results of its application have been promising.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 9 publications
1
21
0
Order By: Relevance
“…Due to the improvement of neuroendoscopic systems and instruments, recent series have shown high rates of hematoma evacuation that ranged from 83.4% to 99%. 3,4,[8][9][10]12 The hematoma evacuation rate in the present study is comparable to what has been reported in the literature. We do think that there is a trend toward a higher evacuation rate when the surgery is performed early (within 12 hours) due to the fact that, within this period, the clot is usually easily suctioned (in contrast to the treatment of subacute hematomas).…”
Section: Outcome Improvement With Early and Complete Hematoma Evacuationsupporting
confidence: 81%
See 3 more Smart Citations
“…Due to the improvement of neuroendoscopic systems and instruments, recent series have shown high rates of hematoma evacuation that ranged from 83.4% to 99%. 3,4,[8][9][10]12 The hematoma evacuation rate in the present study is comparable to what has been reported in the literature. We do think that there is a trend toward a higher evacuation rate when the surgery is performed early (within 12 hours) due to the fact that, within this period, the clot is usually easily suctioned (in contrast to the treatment of subacute hematomas).…”
Section: Outcome Improvement With Early and Complete Hematoma Evacuationsupporting
confidence: 81%
“…It also avoids the early collapse of the hematoma cavity with residual hematoma that may need the inflation-deflation method to solve this problem. 8 The selection of the approach (the frontal or temporal approach) for putaminal ICH is an important issue. Hsieh et al 4 mentioned that, in patients with ICH volume less than 50 ml, it is not difficult to evacuate the hematoma through the shortest distance from the cortical surface to the hematoma.…”
Section: Comparison With Different Methods Of Endoscope-assisted Ich mentioning
confidence: 99%
See 2 more Smart Citations
“…The last decade has brought significant advances in endoscopic surgical instruments and techniques that have improved patient outcomes (12,16,20). Recent reports on the rate of hematoma evacuation through endoscopic surgery have reached rates of 99% (15,17), and comparative studies about minimally invasive surgery and craniotomy are still rare. We believe that as long as the positioning is accurate, keyhole endoscopic surgery can achieve the effect of large craniotomy surgery.…”
Section: Endoscopic Surgerymentioning
confidence: 99%